Papillomatous epidermal nevus with papillary hemorrhages. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
Epidermal nevus is a clonal proliferation of keratinocytes (3). The larger it is, the more precociously it arose during the fetal life. The smallest epidermal nevi can get visible after birth (2) and should be differentiated from melanocytic nevi, seborrheic warts and common warts. The dermal papillomatous melanocytic nevus can be indistinguishable from epidermal nevus except for its histological findings. Seborrheic wart can be indistinguishable from an epidermal nevus also with a histological examination. However, the former is characterized by family history, later onset and multiple lesions with different distribution. Common warts, although clinically and dermoscopically superimposable to epidermal nevus, can be differentiated from the latter due to their different clinical course.